Reciclagem química do PVC: aplicação do PVC parcialmente desidroclorado para a produção de um trocador iônico - Santos, Helena Maria de Almeida Mattos Martins dos (2009)
Poly(vinyl chloride) (PVC) pipes were chemically modified aiming at the production of a sulfonated polymer, using dehydrochlorinated PVC samples as intermediates. Two intermediates were formed: (1) partially dehydrochlorinated PVC with long sequences of conjugated double bonds and (2) the product of partial dehydrochlorination of PVC and nucleophilic substitution of chlorine by hydroxyl groups. The infrared spectra showed that dehydrochlorinated samples are heterogeneous materials, showing different proportions of elimination products, hydroxyl substitution and partial oxidation. Samples dehydrochlorinated with PEG 400 (DPVCA) for 24 hours and PEG 400 for 15 minutes (DPVCD) showed the highest sulfonation yield, what is related to the sulfonation mechanism occurring predominantly due to the presence of hydroxyl groups in a mixture of vinyl alcohol and vinyl chloride units. The sulfonation was confirmed by the presence of a medium intensity band at 1180 cm-1 assigned to sulfonic groups. Both materials showed ion exchange properties but DPVCD is a more promissory material due the value obtained 1.125 mmols/g. These results show that the discarded PVC can be modified chemically to produce a new material with new perspectives to the work as ion exchanger.